2017
DOI: 10.1038/labinvest.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits colitis-associated tumorigenesis via suppressing inflammatory responses and the consequent EGFR signaling-involved tumor cell growth

Abstract: The anti-inflammatory and anti-tumor effects of berberine, a traditional Chinese medicine, were separately discovered in pathological intestinal tissues. However, whether the anti-inflammatory effect of berberine contributes to its anti-tumor effect on colitis-associated colorectal cancer (CACRC) remains unknown. In the present study, we found that berberine effectively inhibited colitis-associated tumorigenesis and colonic epithelium hyperproliferation in dextran sulfate sodium (DSS)-treated Apc mice. A mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 35 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…It has been used for the treatment of intestinal infections for a long time in China and is one of the most popular herbal supplements for children in America [ 11 ]. Accumulating evidence has proven that BBR can suppress colon epithelial proliferation and tumorigenesis through the inhibition of epidermal growth factor receptor (EGFR) signaling, the phosphorylation of signal transducer and activator of transcription 3 (STAT3), and the activation of AMP-activated protein kinase (AMPK) [ 12 , 13 , 14 ]. However, we cannot fully explain its clinical efficacy, because its bioavailability is very low as a result of poor solubility and membrane permeability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for the treatment of intestinal infections for a long time in China and is one of the most popular herbal supplements for children in America [ 11 ]. Accumulating evidence has proven that BBR can suppress colon epithelial proliferation and tumorigenesis through the inhibition of epidermal growth factor receptor (EGFR) signaling, the phosphorylation of signal transducer and activator of transcription 3 (STAT3), and the activation of AMP-activated protein kinase (AMPK) [ 12 , 13 , 14 ]. However, we cannot fully explain its clinical efficacy, because its bioavailability is very low as a result of poor solubility and membrane permeability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has emerged, illuminating anti-cancer effects of phytochemical-berberine (BBR) [ 6 ], which is an isoquinoline type of botanical alkaloid present in many traditional Chinese medicines as the major bioactive compound. BBR has several potent pharmacological functions and has been used for its antidiabetic, antimicrobial, antidiabetic, antidiarrheal and anti-inflammatory activities [ 7 , 8 , 9 ]. Additionally, BBR has been reported to possess anti-tumor activity in multiple types of cancers including HCC [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, BBR has drawn extensive attention due to its antitumorigenic effects in various types of human cancer cells and animal models (33,34). Treatment with BBR has been reported to act on numerous targets and signaling pathways underlying pathophysiological process, including proliferation, apoptosis, angiogenesis, migration and invasion in a variety of cancer cells (35)(36)(37). In our previous study, BBR was observed to exert a strong inhibitory effect on hERG potassium channels (22,38,39), which are often aberrantly expressed in carcinoma.…”
Section: Discussionmentioning
confidence: 99%